Peningkatan Mutu Pendidikan Melalui Manajemen Full Day School Pada SD Full Day - Susanti, Ari; Asrofi, Imam (IAIN Syekh Nurjati Cirebon, 2021)
Technology affects moral and social values in society, coupled with the lack of time provided by parents to accompany their children. With a full day school system, it is considered capable of providing a balanced portion of religious-based scientific fields to students. The purpose of the study was to determine management in the implementation of full day school schools. This research method uses a qualitative approach. The results of this study indicate that education planning with a full day school system in Bandung City Elementary School covers the fields of curriculum, teaching staff, infrastructure, students and financing. The curriculum used is basically the same, namely the compulsory content curriculum, local content curriculum, and additional content curriculum, which only distinguishes the division of time allocation and how to reduce subjects so that they are in line between the compulsory content curriculum and the additional curriculum that is a characteristic or superior program in each of these schools. The implementation of education with a full day school system at Elementary School in Bandung City includes the following components: motivation, leadership type and decision-making techniques. The provision of motivation is carried out every day after school hours through upgrading activities to prepare materials and learning media the next day, the principal also conducts weekly coaching, there is also monthly coaching carried out by the foundation. The evaluation system used is divided into daily evaluations, monthly evaluations, quarterly evaluations, and semester evaluations.Keyword: Management, Full Day School, Quality of Education